HEGEMONI PENGHULU NAGARI DALAM PROSES PENJUALAN TANAH PUSAKA TINGGI KAUM DATUK MANILIK The Hegemony of Penghulu Nagari in the Selling Process ofusakaTinggiLand of Datuk Manilik ICaum - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT This research explains the hegemony process of penghulu nagari over kaum society on the selling process of pusaka tinggi land belonged to kaum of Datuk Manilik, where Anai Resort & Golf Course (NGRC) has developed as a tourism area in West Sumetera. This process acquired Datuk Manilik kaum to sell 50 ha of their pusaka tinggi land. The invoke of penghulu nagari toward the selling process do not match the their traditional role to maintain and protect the existence of pusaka tinggi land or ulayat land of kaum society. This research has identifies two levels of hegemony of the selling process. On the first level, there is the government hegemony over penghulu nagari through Perda No. 13/1983 and Perda No. 8/1994 whence the existence, roles, and functions of penghulu nagari within ingenious society were justified. Both the rules successfully places penghulu nagari as the translator of all the government policies in the social and cultural area to support the government and other groups programs â including the NGRC development -that invokes the Indonesia government policies. The second level is the hegemony of the penghulu nagari over kaum society through defining the consensus of all penghulus in that area as a cultural legitimation to justify the selling process. These circumtances implicate a process of commodification of pusaka tinggi land, reducing the centrality of penghulu kaum supremacy, strengthening the kaum members individuality, and the undermining of the social relationship based on the existence of the pusaka tinggi land. Keywords: penghulu nagari â hegemony â pusaka tinggi land.